Waterproof anti-cracking composite coiled material as well as preparation method and application thereof
By applying an esterified modified waterproof finisher to the decorative paper, the problems of easy bending and fragmentation during bonding and poor waterproof performance are solved, and the effects of high flexibility, crack resistance and tensile strength are achieved.
Patent Information
- Application Number
- CN202411753851.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
AI Technical Summary
Existing decorative papers are difficult to take into account multiple aspects such as waterproofing, flexibility, and tensile strength, which leads to easy bending and fragmentation during bonding, and poor waterproof performance.
The waterproof finishing agent consisting of epoxy resin, hardener, rubber particles, modified bacterial cellulose, polylactic acid, polyethylene glycol and silane coupling agent is used to improve the flexibility and mechanical strength of the waterproof coating by esterification.
The flexibility and crack resistance of the composite coil during bonding are achieved, which avoids bending and fragmentation, and improves waterproof performance and ensures the overall performance of the decorative material.
Smart Images

Figure CN119565893A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of decorative paper materials, and in particular to a waterproof and crack-resistant composite coiled material and a preparation method and application thereof. Background Art
[0002] Decorative paper is a material widely used in furniture and interior decoration. With its various patterns, colors and textures, it is often used for the surface decoration of panel furniture, such as medium-density fiberboard (MDF), particleboard, etc. It can imitate wood grain, stone grain, abstract patterns or plain colors, etc., providing rich visual effects. Decorative paper can also be used for wall decoration, providing beautiful patterns and colors to enhance the decorative effect of the interior.
[0003] Decorative paper itself has a certain degree of water absorption and is easily affected by moisture, resulting in deformation, fading or damage. The traditional waterproofing method is to apply a wet strength agent on the surface of the paper. If the amount of wet strength agent added is too high, the paper may become stiff and affect its flexibility. And if the wet strength agent is unevenly distributed in the paper, it may cause inconsistent local strength of the paper, thereby affecting its overall performance. Existing decorative paper is difficult to take into account multiple aspects such as waterproofing, flexibility, and tensile strength. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a waterproof and crack-resistant composite coiled material that can simultaneously take into account waterproofness, flexibility, and good tensile strength performance, as well as a preparation method and application thereof.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] In a first aspect, the present invention provides a waterproof and crack-resistant composite coiled material, comprising a paper base and a waterproof coating coated on the surface of the paper base, wherein the waterproof coating is formed by curing a waterproof finishing agent, wherein the waterproof finishing agent comprises the following raw materials in parts by weight: 60-75 parts of epoxy resin, 2-5 parts of hardener, 5-20 parts of rubber particles, 8-15 parts of modified bacterial cellulose, 20-30 parts of polylactic acid, 10-20 parts of polyethylene glycol and 5-10 parts of silane coupling agent; the preparation method of the waterproof finishing agent is to mix and stir the raw materials at 20-40° C. until they are uniformly mixed;
[0007] The modified bacterial cellulose comprises the following raw materials in parts by mass: 1-5 parts of dehydrated bacterial cellulose and 15-100 parts of a modifier, wherein the modifier comprises glycerol, succinic acid and sodium hypophosphite in a mass ratio of (0.08-0.2):1:1; the preparation method of the modified bacterial cellulose comprises the following steps: mixing the dehydrated bacterial cellulose and the modifier, and heating at 80-100°C to obtain the modified bacterial cellulose.
[0008] Bacterial cellulose has very high strength and rigidity, and its performance is comparable to that of glass fiber and carbon fiber, and even higher than that of some conventional engineering plastics. Therefore, when bacterial cellulose is added to a coating, it can significantly improve the rigidity of the coating. However, if the rigidity is too high, it will affect the flexibility of the waterproof coating and the fit of the composite coil to furniture. Therefore, the present invention esterifies bacterial cellulose. In the esterification reaction of bacterial cellulose, glycerol can be used as a plasticizer to improve the flexibility and ductility of cellulose, succinic acid can be used as a reactant or catalyst to participate in the esterification reaction, and sodium hypophosphite is used as a catalyst to promote the esterification reaction. The interaction force between the molecular chains of the esterified bacterial cellulose is enhanced, thereby improving the tensile strength and toughness of cellulose, and effectively reducing the bending rigidity of the bacterial cellulose, thereby improving the softness of the waterproof coating and avoiding the bending and breaking of the decorative paper during lamination.
[0009] The addition of polylactic acid (PLA) and polyethylene glycol (PEG) can improve the wettability and fluidity of the coating on the paper surface, which helps the coating to adhere and penetrate evenly on the paper surface. The molecular chain structure of PLA gives it certain strength and toughness. When PLA is added to the coating, PEG can be used as a compatibilizer for PLA, which promotes PLA to penetrate into the fiber structure of the paper and enhance the bonding force between the fibers, thereby improving the strength and toughness of the paper.
[0010] Esterified cellulose is obtained by esterification reaction between the hydroxyl groups of cellulose molecules and acids or anhydrides, while polylactic acid is obtained by polycondensation reaction of lactic acid molecules. Therefore, both esterified cellulose and polylactic acid contain ester groups and have certain compatibility in chemical structure. The two can be physically entangled in the presence of polyethylene glycol to form a stable network structure, which can effectively improve the mechanical strength of waterproof coatings.
[0011] Silane coupling agents can penetrate into the fiber structure on the surface of paper, improve the interaction between fibers, and increase the strength and wear resistance of paper. The self-crosslinking of silane and PEG that penetrate into the paper base improves the crystallization of PLA, and can increase the crystallization rate and crystallinity of PLA. Fast crystallization means that a complete crystal structure can be formed more quickly during processing, thereby improving the thermal and mechanical properties of the waterproof coating. The paper base contains a large amount of wood cellulose, and the silane coupling agent will form more reactive sites on the cellulose surface, which is conducive to forming a stronger chemical bond with the epoxy resin, thereby improving the bonding strength between the waterproof coating and the paper base.
[0012] At the same time, the epoxy resin added to the waterproof coating itself has a high hardness, but relatively poor toughness. The rubber particles have good flexibility and elasticity. When the epoxy resin is mixed with the rubber particles, the rubber particles can absorb and disperse the energy generated by the coating when it is impacted by external forces, thereby effectively preventing the waterproof coating from cracking and breaking.
[0013] Preferably, the epoxy resin is a glycidyl ester epoxy resin.
[0014] Preferably, the rubber particles are polyamide rubber, and have a size of 5-20 μm, more preferably 10 μm.
[0015] Preferably, the weight average molecular weight M of the polyethylene glycol is w =1000-2000 g / mol, more preferably 1500 g / mol.
[0016] Preferably, the dehydrated bacterial cellulose needs to be activated before modification, and the activation treatment is: soak the dehydrated bacterial cellulose in alkali solution for 12 to 24 hours, then add acid solution to adjust the pH to 6 to 7, and dry it after taking it out. The reason for activation before modification: the alkali solution can react with the acidic functional groups (such as carboxyl groups) in the cellulose molecules to neutralize, thereby introducing new hydroxyl groups. At the same time, the strong alkalinity of the alkali solution and the swelling effect of soaking in the alkaline solution can destroy the hydrogen bonds between cellulose molecules, so that more hydroxyl groups are exposed to the reaction environment, which is beneficial to subsequent surface modification and modification. The activation treatment can also increase the roughness of the bacterial cellulose surface to a certain extent, so that its contact area with other materials is increased, which is conducive to forming a closer bond. The alkali solution can be a strong alkaline solution such as a sodium hydroxide solution or a potassium hydroxide solution of 1 to 6 mol / L, and the acid solution can be a hydrochloric acid solution, a sulfuric acid solution, or a nitric acid solution of 1 to 6 mol / L.
[0017] Preferably, the method for preparing the modified bacterial cellulose comprises the following steps: mixing the dehydrated bacterial cellulose and the modifier, and heating at 80-100° C. for 40-50 min.
[0018] Preferably, the mass ratio of the dehydrated bacterial cellulose to the modifier in the modified bacterial cellulose is 1:(16-22), and more preferably 1:20.
[0019] Preferably, the silane coupling agent is at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, vinyltriethoxysilane and vinyltrimethoxysilane, more preferably 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane.
[0020] Preferably, the hardener is hardener HY951 and / or hardener HY956.
[0021] In a second aspect, the present invention provides a method for preparing a waterproof and crack-resistant composite coiled material, comprising the following steps:
[0022] The waterproof finishing agent is coated on one or both sides of the paper base, and is cured at 90-100 degrees Celsius to form a waterproof coating on the surface of the paper base, thereby obtaining the waterproof and crack-resistant composite coiled material.
[0023] Preferably, the coating amount of the waterproof finishing agent on each side of the paper base is 5-15 g / m 2 If the coating is too thick, it will affect the softness, and if the coating is too thin, it will affect the mechanical strength.
[0024] In a third aspect, the present invention provides a waterproof and crack-resistant composite coiled material for preparing decorative materials.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The waterproof coating on the paper base of the present invention is solidified by a waterproof finishing agent; the main raw materials of the waterproof finishing agent are: epoxy resin, hardener, rubber particles, modified bacterial cellulose, polylactic acid, polyethylene glycol and silane coupling agent; the modified bacterial cellulose is esterified, which can effectively reduce the bending stiffness of the bacterial cellulose, thereby improving the softness of the waterproof coating and preventing the decorative paper from bending and breaking during lamination. Esterified cellulose and polylactic acid have certain compatibility in chemical structure, and the two can be physically entangled in the presence of polyethylene glycol to form a stable network structure, which can effectively improve the mechanical strength of the waterproof coating. The self-crosslinking of silane and PEG infiltrated into the paper base improves the crystallization of PLA, and can increase the crystallization rate and crystallinity of PLA. The fast crystallization rate means that a perfect crystalline structure can be formed faster during the processing, thereby improving the thermal and mechanical properties of the waterproof coating. The rubber particles make up for the poor toughness of epoxy resin. The epoxy resin and rubber particles can make the waterproof coating have both hardness, flexibility and elasticity, which can effectively prevent the waterproof coating from cracking and damage.
[0027] (2) The composite coil of the present invention can be used as a decorative material attached to the surface of furniture because it has good flexibility, crack resistance and tensile resistance, thereby overcoming the technical problems of traditional furniture decorative paper being easily bent and broken at the corners when attached and having poor waterproof performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a physical picture of the composite coil of the present invention. DETAILED DESCRIPTION
[0029] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0030] In the following examples and comparative examples, the sources of the raw materials used are as follows:
[0031] Paper base: kraft paper, manufacturer: Dongguan Yingxin Paper Co., Ltd., brand number 026, width 1092mm, thickness 30g;
[0032] Epoxy resin: Glycidyl ester epoxy resin, 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester, manufactured by Tianjin Jingdong Chemical Composite Materials Co., Ltd., brand name TDE-90;
[0033] Rubber particles: polyamide rubber, the manufacturer is Dongguan Wanhe Plastic Raw Materials Co., Ltd., the brand is 6333SA01MED PA12;
[0034] Bacterial cellulose: milky white gel-like appearance, length 10000-20000nm, diameter 50-100nm, manufacturer is Shanghai Puzhen Biotechnology Co., Ltd., brand number is Kramar 210303134246;
[0035] Succinic acid: manufacturer is Sigma-Aldrich (Shanghai) Trading Co., Ltd., brand number 14079;
[0036] Sodium hypophosphite: manufacturer is Sigma-Aldrich (Shanghai) Trading Co., Ltd., brand number 04434;
[0037] Polylactic acid: The manufacturer is Anhui Fengyuan Polylactic Acid Co., Ltd., and the brand is Anhui Fengyuan FY804;
[0038] Polyethylene glycol: weight average molecular weight M w = 1000 g / mol, 1500 g / mol, 2000 g / mol polyethylene glycol were purchased from Shandong Leli New Materials Co., Ltd.:
[0039] Unless otherwise specified, other materials, reagents, etc. used in the examples and comparative examples can be obtained from commercial sources.
[0040] Example 1
[0041] A waterproof and crack-resistant composite coiled material, comprising a paper base and a waterproof coating coated on the surface of the paper base, wherein the waterproof coating is formed by curing a waterproof finishing agent, wherein the waterproof finishing agent comprises the following raw materials in parts by weight: 70 parts of epoxy resin, 3 parts of hardener, 18 parts of rubber particles, 10 parts of modified bacterial cellulose, 25 parts of polylactic acid, 15 parts of polyethylene glycol and 6 parts of silane coupling agent, wherein the epoxy resin is a glycidyl ester epoxy resin, the hardener is a hardener HY951, the rubber particles are polyamide rubber, and the weight average molecular weight of the polyethylene glycol is Mw =1500 g / mol, the silane coupling agent is 3-aminopropyltriethoxysilane; the preparation method of the waterproof finishing agent is to mix and stir the raw materials at 30°C.
[0042] The modified bacterial cellulose comprises the following raw materials in parts by mass: 1 part of dehydrated bacterial cellulose and 20 parts of a modifier, that is, the mass ratio of the dehydrated bacterial cellulose to the modifier in the modified bacterial cellulose is 1:20, and the modifier comprises glycerol, succinic acid, and sodium hypophosphite in a mass ratio of 0.1:1:1;
[0043] The preparation method of modified bacterial cellulose comprises the following steps: firstly immersing dehydrated bacterial cellulose in a 2 mol / L sodium hydroxide solution of twice its mass for 20 hours, then adding a 5 mol / L hydrochloric acid solution to adjust the pH to 7, taking out and drying, mixing the dehydrated bacterial cellulose and a modifier, and heating at 90°C for 45 minutes.
[0044] The preparation method of the waterproof and crack-resistant composite coiled material comprises the following steps:
[0045] The waterproof finishing agent is coated on both sides of the paper base and cured at 95°C to form a waterproof coating on the surface of the paper base, thereby obtaining the waterproof and crack-resistant composite coiled material. The coating amount on each side is controlled at 10 g / m 2 .
[0046] Example 2
[0047] A waterproof and crack-resistant composite coiled material, comprising a paper base and a waterproof coating coated on the surface of the paper base; the waterproof coating is formed by curing a waterproof finishing agent, the waterproof finishing agent comprising the following raw materials in parts by mass: 60 parts of epoxy resin, 2 parts of hardener, 5 parts of rubber particles, 8 parts of modified bacterial cellulose, 20 parts of polylactic acid, 10 parts of polyethylene glycol and 5 parts of silane coupling agent, the epoxy resin is a glycidyl ester epoxy resin, the hardener is a hardener HY951, the rubber particles are polyamide rubber, and the weight average molecular weight of the polyethylene glycol is M w =1000 g / mol, the silane coupling agent is 3-aminopropyltrimethoxysilane; the preparation method of the waterproof finishing agent is to mix and stir the raw materials at 20°C.
[0048] The modified bacterial cellulose comprises the following raw materials in parts by mass: 1 part of dehydrated bacterial cellulose and 15 parts of a modifier, that is, the mass ratio of the dehydrated bacterial cellulose to the modifier in the modified bacterial cellulose is 1:15, and the modifier comprises glycerol, succinic acid, and sodium hypophosphite in a mass ratio of 0.08:1:1;
[0049] The preparation method of modified bacterial cellulose comprises the following steps: firstly immersing dehydrated bacterial cellulose in a 1 mol / L potassium hydroxide solution of twice its mass for 24 hours, then adding a 1 mol / L nitric acid solution to adjust the pH to 6, taking out and drying, mixing the dehydrated bacterial cellulose and a modifier, and heating at 80°C for 50 minutes.
[0050] The preparation method of the waterproof and crack-resistant composite coiled material comprises the following steps:
[0051] The waterproof finishing agent is coated on both sides of the paper base and cured at 90°C to form a waterproof coating on the surface of the paper base, thereby obtaining the waterproof and crack-resistant composite coiled material. The coating amount on each side is controlled at 5g / m 2 .
[0052] Example 3
[0053] A waterproof and crack-resistant composite coiled material, comprising a paper base and a waterproof coating coated on the surface of the paper base; the waterproof coating is formed by curing a waterproof finishing agent, the waterproof finishing agent comprising the following raw materials in parts by weight: 75 parts of epoxy resin, 5 parts of hardener, 20 parts of rubber particles, 15 parts of modified bacterial cellulose, 30 parts of polylactic acid, 20 parts of polyethylene glycol and 10 parts of silane coupling agent, the epoxy resin is a glycidyl ester epoxy resin, the hardener is a hardener HY956, the rubber particles are polyamide rubber, and the weight average molecular weight of the polyethylene glycol is M w =2000 g / mol, the silane coupling agent is vinyl triethoxysilane; the preparation method of the waterproof finishing agent is to mix and stir the raw materials at 40°C.
[0054] The modified bacterial cellulose comprises the following raw materials in parts by mass: 5 parts of dehydrated bacterial cellulose and 100 parts of modifier, that is, the mass ratio of dehydrated bacterial cellulose to modifier in the modified bacterial cellulose is 1:20, and the modifier comprises glycerol, succinic acid and sodium hypophosphite in a mass ratio of 0.2:1:1.
[0055] The preparation method of modified bacterial cellulose comprises the following steps: firstly immersing dehydrated bacterial cellulose in a 6 mol / L sodium hydroxide solution of twice its mass for 12 hours, then adding a 6 mol / L sulfuric acid solution to adjust the pH to 7, taking out and drying, mixing the dehydrated bacterial cellulose and a modifier, and heating at 100°C for 40 minutes.
[0056] The preparation method of the waterproof and crack-resistant composite coiled material comprises the following steps:
[0057] The waterproof finishing agent is coated on one side of the paper base and cured at 100°C to form a waterproof coating on the surface of the paper base, thereby obtaining the waterproof and crack-resistant composite coiled material. The coating amount on each side is controlled at 15g / m2 .
[0058] Example 4
[0059] The difference between Example 4 and Example 1 is that the silane coupling agent in Example 4 is vinyl triethoxy silane.
[0060] Example 5
[0061] The difference between Example 5 and Example 1 is that the weight average molecular weight M of the polyethylene glycol is w It is 1000g / mol.
[0062] Example 6
[0063] The difference between Example 6 and Example 1 is that the weight average molecular weight M of the polyethylene glycol is w It is 2000g / mol.
[0064] Example 7
[0065] The difference between Example 7 and Example 1 is that the weight average molecular weight M of the polyethylene glycol is w It is 2500g / mol.
[0066] Example 8
[0067] The difference between Example 8 and Example 1 is that the total amount of dehydrated bacterial cellulose and the modifier in the modified bacterial cellulose remains unchanged, and the mass ratio of dehydrated bacterial cellulose to the modifier is 1:15.
[0068] Example 9
[0069] The difference between Example 9 and Example 1 is that the total amount of dehydrated bacterial cellulose and the modifier in the modified bacterial cellulose remains unchanged, and the mass ratio of dehydrated bacterial cellulose to the modifier is 1:16.
[0070] Example 10
[0071] The difference between Example 10 and Example 1 is that the total amount of dehydrated bacterial cellulose and modifier in the modified bacterial cellulose remains unchanged, and the mass ratio of dehydrated bacterial cellulose to modifier in the modified bacterial cellulose is 1:22.
[0072] Embodiment 11
[0073] The difference between Example 11 and Example 1 is that the total amount of dehydrated bacterial cellulose and the modifier in the modified bacterial cellulose remains unchanged, and the mass ratio of dehydrated bacterial cellulose to the modifier in the modified bacterial cellulose is 1:23.
[0074] Example 12
[0075] The difference between Example 12 and Example 1 is that the modified bacterial cellulose is not activated before modification.
[0076] Embodiment 13
[0077] The difference between Example 13 and Example 1 is that the coating amount of the waterproof finishing agent on each side is 5g / m 2 .
[0078] Embodiment 14
[0079] The difference between Example 14 and Example 1 is that the coating amount of the waterproof finishing agent on each side is 20 g / m 2 .
[0080] Comparative Example 1
[0081] The difference between Comparative Example 1 and Example 1 is that modified bacterial cellulose, polylactic acid and polyethylene glycol are not added to the waterproof finishing agent of Comparative Example 1.
[0082] Comparative Example 2
[0083] The difference between Comparative Example 2 and Example 1 is that no modified bacterial cellulose is added to the waterproof finishing agent of Comparative Example 2.
[0084] Comparative Example 3
[0085] The difference between Comparative Example 3 and Example 1 is that polylactic acid is not added in Comparative Example 3.
[0086] Comparative Example 4
[0087] The difference between Comparative Example 4 and Example 1 is that polyethylene glycol is not added in Comparative Example 4.
[0088] Comparative Example 5
[0089] The difference between Comparative Example 5 and Example 1 is that the bacterial cellulose in Comparative Example 5 is not modified, that is, only bacterial cellulose is added.
[0090] Comparative Example 6
[0091] The difference between Comparative Example 6 and Example 1 is that no glycerol is added to the modified bacterial cellulose in Comparative Example 6.
[0092] Comparative Example 7
[0093] The difference between Comparative Example 7 and Example 1 is that succinic acid and sodium hypophosphite are not added to the modified bacterial cellulose in Comparative Example 7.
[0094] Comparative Example 8
[0095] The difference between Comparative Example 8 and Example 1 is that no silane coupling agent, polylactic acid and polyethylene glycol are added to the waterproof finishing agent of Comparative Example 8.
[0096] Comparative Example 9
[0097] The difference between Comparative Example 9 and Example 1 is that no silane coupling agent is added to the waterproof finishing agent of Comparative Example 9.
[0098] Comparative Example 10
[0099] The difference between Comparative Example 10 and Example 1 is that the paper base layer in Comparative Example 10 is replaced by a PET layer.
[0100] Comparative Example 11
[0101] The difference between Comparative Example 11 and Example 1 is that epoxy resin and rubber particles are not added to the waterproof finishing agent of Comparative Example 11.
[0102] Comparative Example 12
[0103] The difference between Comparative Example 12 and Example 1 is that no epoxy resin is added to the waterproof finishing agent of Comparative Example 12.
[0104] Comparative Example 13
[0105] The difference between Comparative Example 13 and Example 1 is that no rubber particles are added to the waterproof finishing agent of Comparative Example 13.
[0106] Comparative Example 14
[0107] The difference between Comparative Example 14 and Example 1 is that epoxy resin, rubber particles and modified bacterial cellulose are not added to the waterproof finishing agent of Comparative Example 14, that is, the waterproof finishing agent only contains polylactic acid, polyethylene glycol and silane coupling agent.
[0108] Performance Testing
[0109] The composite coils of Examples 1 to 14 and Comparative Examples 1 to 14 were subjected to the following method, wherein a blank control group was also provided, i.e., only a paper base layer was present without coating of a waterproof finishing agent.
[0110] Folding fastness: QB / T4046-2010 is used to test the folding fastness (25°C, 35,000 times) and observe whether there are cracks on the surface.
[0111] Water absorption: GB / T1540 Determination of water absorption of paper and paperboard (Kebo method) is used for testing.
[0112] Tensile strength: GB / T12914 Determination of tensile strength of paper and paperboard (constant rate tensile method) was used for testing.
[0113] Surface bonding strength: GB / T 15102-2017 impregnated paper veneer fiberboard and particleboard were used for testing. See Table 1 for specific data.
[0114] Table 1 Performance data of each group of coils
[0115]
[0116]
[0117] It can be seen from Table 1 that the composite coils of Examples 1 to 14 and Comparative Examples 1 to 14 have good properties of waterproofness, flexibility and tensile strength compared with the paper base layer of the blank control group.
[0118] The various properties of Example 1 are better than those of Example 4, indicating that the performance of 3-aminopropyltriethoxysilane as a silane coupling agent is just better than that of vinyltriethoxysilane.
[0119] Examples 1 and 5 to 7 are to explore the effect of the weight average molecular weight of polyethylene glycol on the performance of the coil. The weight average molecular weight of polyethylene glycol is too low. Low molecular weight polyethylene glycol may reduce the tensile strength, impact strength and wear resistance of the coating because the molecular chain is short and the interaction between molecules is weakened. When the weight average molecular weight of polyethylene glycol is high, the fluidity of the coating in the molten state will deteriorate, making the coating processing more difficult and even affecting the uniformity and flatness of the coating. Combined with the data, it can be seen that the weight average molecular weight of polyethylene glycol M w It is preferably 1000 to 2000 g / mol, more preferably 1500 g / mol.
[0120] Examples 1 and 8 to 11 are intended to explore the mass ratio range of dehydrated bacterial cellulose and modifier in modified bacterial cellulose. The amount of both added affects the degree of esterification. A low degree of esterification will naturally affect the performance, but the crystallinity of esterified cellulose with a higher degree of esterification is usually reduced, resulting in a decrease in the silkiness and mechanical properties of cellulose. Therefore, moderate esterification can reduce the crystallinity of cellulose and improve its processing properties, which is beneficial to the preparation and coating of the coating. Combined with the data, it can be seen that when the mass ratio of dehydrated bacterial cellulose and modifier in the modified bacterial cellulose is 1: (16 to 22), good effects can be achieved in terms of water resistance, flexibility and tensile strength, and the most preferred ratio is 1: 20.
[0121] Embodiment 12 Compared with embodiment 1, the modified bacterial cellulose is not activated before modification, and its waterproofness, flexibility, bonding strength and tensile strength are significantly reduced. This is because the alkali solution can react with the acidic functional groups (such as carboxyl) in the cellulose molecules to neutralize, thereby introducing new hydroxyl groups. At the same time, the strong alkalinity of the alkali solution and the swelling effect of soaking in the alkaline solution can destroy the hydrogen bonds between the cellulose molecules, so that more hydroxyl groups are exposed in the reaction environment, which is conducive to subsequent surface modification and modification. The activation treatment can also increase the roughness of the bacterial cellulose surface to a certain extent, so that its contact area with other materials increases, which is conducive to forming a closer combination.
[0122] The waterproof finishing agent of Comparative Example 1 does not contain modified bacterial cellulose, polylactic acid and polyethylene glycol, and its performance is worse than that of Comparative Examples 2 to 4, indicating that modified bacterial cellulose, polylactic acid and polyethylene glycol have a synergistic effect. This may be because modified bacterial cellulose and polylactic acid are compatible, and the two can be physically entangled in the presence of polyethylene glycol to form a stable network structure. The three can work together to effectively improve the mechanical strength and flexibility of the waterproof coating.
[0123] Example 1 and Comparative Examples 5 to 7 are to explore the effect of the modification method of modified bacterial cellulose on product performance. Comparative Example 6 does not add glycerol, and the flexibility of its waterproof coating is reduced, indicating that glycerol can be used as a plasticizer to improve the flexibility and ductility of cellulose. In Comparative Example 7, succinic acid and sodium hypophosphite are not added, which means that the bacterial cellulose is not esterified, and its waterproof, tensile strength, flexibility and bonding strength are significantly reduced, indicating that the interaction force between the molecular chains of the esterified bacterial cellulose is enhanced, and the performance of the waterproof coating is improved. In Comparative Example 5, only bacterial cellulose is added, and glycerol, succinic acid and sodium hypophosphite are not added. Its performance is worse than that of Comparative Examples 6 to 7, so the components in the modifier in the modified bacterial cellulose have a synergistic effect. The combination of glycerol, succinic acid and sodium hypophosphite can improve the tensile strength and toughness of cellulose, and can effectively reduce the bending stiffness of bacterial cellulose, thereby improving the softness of the waterproof coating.
[0124] The waterproof finishing agent of Comparative Example 8 does not add silane coupling agent, polylactic acid and polyethylene glycol, and its performance is worse than that of Comparative Examples 3-4 and Comparative Example 9, indicating that silane coupling agent, polylactic acid and polyethylene glycol have a synergistic effect on the paper base. First, the addition of polylactic acid (PLA) and polyethylene glycol (PEG) can improve the wettability and fluidity of the coating on the paper surface. The silane coupling agent penetrates into the paper base, and the self-crosslinking of silane and PEG improves the crystallization of PLA, which can increase the crystallization rate and crystallinity of PLA. The fast crystallization rate means that a perfect crystalline structure can be formed more quickly during the processing, thereby improving the thermal and mechanical properties of the waterproof coating. Comparative Example 10 replaces the paper base with PET, and its mechanical properties are reduced. This is because the reaction between cellulose and silane coupling agent is relatively easy and has good controllability; while PET has a stable molecular structure and its surface ester group has low reactivity, so it is difficult to react with silane coupling agent, and usually requires a higher temperature and the assistance of a catalyst to promote the reaction. This is mainly due to the differences in the molecular structures of cellulose and PET and the different reactivity of surface functional groups.
[0125] The waterproof finishing agent of Comparative Example 11 does not contain epoxy resin and rubber particles. Compared with Comparative Examples 12 and 13, the performance of the composite coil is worse, indicating that the epoxy resin and the rubber particles have a synergistic effect. The epoxy resin itself has high impact resistance and hardness, but relatively poor toughness, while the rubber particles have good flexibility and elasticity. The combination of the two makes the waterproof coating have both good flexibility and good mechanical properties.
[0126] The waterproof finishing agent of Comparative Example 14 does not contain epoxy resin, rubber particles, modified bacterial cellulose and polylactic acid, that is, the waterproof finishing agent contains only polylactic acid, polyethylene glycol and silane coupling agent. By comparing it with Comparative Example 8, the blank control group and Example 1, it can be seen that there is a synergistic effect between epoxy resin, rubber particles, modified bacterial cellulose, polylactic acid, polyethylene glycol and silane coupling agent, and the combination of these ingredients can effectively improve the flexibility and mechanical properties of the waterproof coating.
[0127] In summary, if Figure 1 As shown, the composite coil of the present invention can be attached to the surface of furniture as a decorative material because it has good flexibility, crack resistance and tensile resistance, and overcomes the technical problems of traditional furniture decorative paper that is easy to bend and break at the corners when attached and has poor waterproof performance.
[0128] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A waterproof and crack-resistant composite coiled material, characterized in that: The invention comprises a paper base and a waterproof coating coated on the surface of the paper base, wherein the waterproof coating is formed by curing a waterproof finishing agent, and the waterproof finishing agent comprises the following raw materials in parts by weight: 60-75 parts of epoxy resin, 2-5 parts of hardener, 5-20 parts of rubber particles, 8-15 parts of modified bacterial cellulose, 20-30 parts of polylactic acid, 10-20 parts of polyethylene glycol and 5-10 parts of silane coupling agent; the preparation method of the waterproof finishing agent is to mix and stir the raw materials at 20-40°C to make them uniform; The modified bacterial cellulose comprises the following raw materials in parts by weight: 1-5 parts of dehydrated bacterial cellulose, 15-100 parts of a modifier, wherein the modifier comprises glycerol, succinic acid, and sodium hypophosphite in a mass ratio of (0.08-0.2):1:1; The preparation method of the modified bacterial cellulose comprises the following steps: mixing dehydrated bacterial cellulose and a modifier, and heating at 80-100° C. to obtain the modified bacterial cellulose.
2. The waterproof and crack-resistant composite coiled material according to claim 1, characterized in that: The waterproof finishing agent includes at least one of (I) to (III): (I) the epoxy resin is a glycidyl ester epoxy resin; (II) The rubber particles are polyamide rubber and have a size of 5-20 μm; (III) The weight average molecular weight M of the polyethylene glycol w =1000~2000g / mol.
3. The waterproof and crack-resistant composite coiled material according to claim 1, characterized in that: The dehydrated bacterial cellulose is activated before modification. The activation treatment is as follows: the dehydrated bacterial cellulose is immersed in an alkaline solution for 12 to 24 hours, then an acid solution is added to adjust the pH to 6 to 7, and then the dehydrated bacterial cellulose is taken out and dried.
4. The waterproof and crack-resistant composite coiled material according to claim 1, characterized in that: The heating time in the preparation method of the modified bacterial cellulose is 40-50 minutes.
5. The waterproof and crack-resistant composite coiled material according to claim 1 or 4, characterized in that: The mass ratio of the dehydrated bacterial cellulose to the modifier is 1:(16-22).
6. The waterproof and crack-resistant composite coiled material according to claim 1, characterized in that: The silane coupling agent is at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, vinyltriethoxysilane and vinyltrimethoxysilane.
7. The waterproof and crack-resistant composite coiled material according to claim 1, characterized in that: The hardener is hardener HY951 and / or hardener HY956.
8. The method for preparing the waterproof and crack-resistant composite coiled material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The waterproof finishing agent is coated on one or both sides of the paper base, and is cured at 90-100° C. to form a waterproof coating on the surface of the paper base, thereby obtaining the waterproof and crack-resistant composite coiled material.
9. The method for preparing the waterproof and crack-resistant composite coiled material according to claim 8, characterized in that: The coating amount of the waterproof finishing agent on each side of the paper base is 5-15g / m 2 .
10. Use of the waterproof and crack-resistant composite coiled material according to any one of claims 1 to 7 in the preparation of decorative materials.
Citation Information
Cited By
Multi-layer composite reinforced door and window frame and preparation method thereof
CN122190597A